„Telegram“ kaip politinės komunikacijos priemonė ir jos naudojimas Rusijos valdančiojo elito rate - Salikov, Alexey (Politologija, 2019)
This article examines the use of Telegram as a means of political communication by the ruling political elite in Russia (both external, i.e., communication with the society and other political forces, and internal, i.e., between different, often rival, groups within the elite itself). While Telegram is illegal at the official level, and attempts have been made to block it in Russia since April 2018, unofficially the Russian authorities continue to actively use Telegram channels for political communication and influencing public opinion as well as for monitoring the mood of the public. What is the reason for this ambivalent attitude toward Telegram? What makes it so attractive for the Russian establishment? How are the authorities using Telegram for their own purposes? Answering these questions is the main goal of this study.
Keywords: „Telegram“; „Telegram“ kanalai; politinė komunikacija; Rusija; Rusijos valdžia; Rusijos politinis elitas